2007
DOI: 10.1002/elan.200703864
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry of Electroinactive Species Using Quinone/Hydroquinone Redox: A Known Redox System Viewed in a New Perspective

Abstract: Electrochemical behavior of p-benzoquinone (Q), hydroquinone (H 2 Q) and quinhydrone complex (QH) have been investigated in aqueous unbuffered solutions. The results revealed that in unbuffered solution the half wave potential of hydroquinone has a significant difference with quinones half wave potential. It shown that, added acid in an unbuffered solution of Q, give rise to a new reduction peak at a more positive potential than original reduction peak of Q. The half-peak potential of this new peak is dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
4
28
0
1
Order By: Relevance
“…3 shows the results of half-cell measurements on para-benzoquinone and parahydroquinone at concentrations of 0.0925 M and 0.0918 M, respectively, in a 1 N H 2 SO 4 solution at 20C. We see prominent reduction and oxidation peaks for the couple at 0.69 V and 0.17 V, respectively, which is consistent with the previously-observed electrochemical behavior of the para-benzoquinone/para-hydroquinone couple [5,6]. The reduction potential is given to be 0.43 V vs. Ag/AgCl electrode, or equivalently, 0.64 V vs. SHE.…”
Section: Half-cell Measurementssupporting
confidence: 86%
“…3 shows the results of half-cell measurements on para-benzoquinone and parahydroquinone at concentrations of 0.0925 M and 0.0918 M, respectively, in a 1 N H 2 SO 4 solution at 20C. We see prominent reduction and oxidation peaks for the couple at 0.69 V and 0.17 V, respectively, which is consistent with the previously-observed electrochemical behavior of the para-benzoquinone/para-hydroquinone couple [5,6]. The reduction potential is given to be 0.43 V vs. Ag/AgCl electrode, or equivalently, 0.64 V vs. SHE.…”
Section: Half-cell Measurementssupporting
confidence: 86%
“…Therefore, after the first electrochemical study of catechol in the presence of 1,3-cyclopentadiene [10], we now report electrochemical study, electrochemical synthesis and kinetic evaluation of oxidation of 1,4-hydroquinone in the presence of 1,3-cyclopentadiene. Previously we have shown that 1,4-hydroquinone can be oxidized electrochemically to p-benzoquinones and the formed quinone can be attacked as Michael acceptors by a variety of nucleophiles [11][12][13][14][15]. In contrast to our previous works, in this work the electro-generated p-benzoquinone is used as a dienophile.…”
Section: Introductionmentioning
confidence: 60%
“…The absence of the reverse peak is likely attributed to the instability of the electro-oxidation produced species in alkaline conditions, as also observed in other works. 61,[64][65][66] Post CV, the half-cell OCP for both species drops below −0.6 V vs. SCE, which suggests the formation and presence of a new species in the solution. Despite these indications that both H 2 BQS and AA may not be reversible under alkaline conditions and hence unsuitable for a conventional flow battery application in alkaline conditions, both are still deemed adequate for the primary battery approach presented in this work, since only the electro-oxidation portion of the cycle is of interest.…”
Section: Resultsmentioning
confidence: 95%